2012
DOI: 10.3791/3844
|View full text |Cite
|
Sign up to set email alerts
|

Genotyping of Plant and Animal Samples without Prior DNA Purification

Abstract: The Direct PCR approach facilitates PCR amplification directly from small amounts of unpurified samples, and is demonstrated here for several plant and animal tissues (Figure 1). Direct PCR is based on specially engineered Thermo Scientific Phusion and Phire DNA Polymerases, which include a double-stranded DNA binding domain that gives them unique properties such as high tolerance of inhibitors.PCR-based target DNA detection has numerous applications in plant research, including plant genotype analysis and ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Whole spider specimens were used to extract DNA with Extraction Solution and Dilution Solution (Sigma-Aldrich, Saint Louis, MO, USA) according to manufacturer protocol. All samples were macerated using sterilised pipette tips (Chum et al, 2012). Ten taxon specific primer pairs, amplifying 200–300 bp long segment of mitochondrial cytochrome-oxidase I (COI) barcoding region was designed using the NCBI Primer-blast home page (http://www.ncbi.nlm.nih.gov/tools/primer-blast/) following the recommendations of King et al (2008) and tested in silico for Psammotettix specificity against GenBank nucleotid database of Arthropoda taxa with the same application.…”
Section: Methodsmentioning
confidence: 99%
“…Whole spider specimens were used to extract DNA with Extraction Solution and Dilution Solution (Sigma-Aldrich, Saint Louis, MO, USA) according to manufacturer protocol. All samples were macerated using sterilised pipette tips (Chum et al, 2012). Ten taxon specific primer pairs, amplifying 200–300 bp long segment of mitochondrial cytochrome-oxidase I (COI) barcoding region was designed using the NCBI Primer-blast home page (http://www.ncbi.nlm.nih.gov/tools/primer-blast/) following the recommendations of King et al (2008) and tested in silico for Psammotettix specificity against GenBank nucleotid database of Arthropoda taxa with the same application.…”
Section: Methodsmentioning
confidence: 99%
“…Here, a direct PCR approach was applied to analyse a cytochrome P450 marker variability in the Europe populations of Hedera helix, L. Amplification of the target sites of plant genome by the direct PCR is a method where no DNA extraction is needed prior the PCR. It is possible to use both, crude plant extract as well as the small pieces of plant tissues without steps of isolation and purification of total genomic DNA (Chum et al, 2012). Omission of the step of DNA isolation process brings benefits mainly in terms of utilization of samples without loss, saving time and reducing the cost of analysis.…”
Section: Introductionmentioning
confidence: 99%
“…This makes DNA analysis by direct PCR methods very difficult, so an additional step is usually required to remove the compounds [25,43]. Direct PCR amplification can be overcome by using a quick and easy dilution protocol, coupled with a unique DNA polymerase that has a double-stranded DNA binding domain [44]. The results showed that it is very efficient to use the small leaf disks for the sex determination of papaya.…”
Section: Resultsmentioning
confidence: 99%